Application of Spiritual Guided Imagery Relaxation Technique to Reduce Anxiety in Patients with Chronic Renal Failure: Case Study - TATA MAHYUVI (Indonesian Journal of Nursing Scientific, 2023)
Patients with chronic kidney failure say that they are worried because they see the tubes flowing blood, the costs that must be incurred each time they undergo therapy, worry because invasive procedures will be carried out and uncertainty about recovery. The purpose of this case study is to carry out nursing care for patients with Chronic Kidney Failure Patients with anxiety nursing problems in the Inpatient Room of A. Yani Surabaya Islamic Hospital. This type of research uses qualitative methods with a case study approach. The subjects used were 1 Chronic Kidney Failure patient who underwent inpatient care with nursing problems for 3 interventions (1 time a day for 10-15 minutes) with data collection methods including assessment, determining diagnoses, making interventions, implementation and evaluation. The results of the case study of the Application of Spiritual Guided Imagery Relaxation Techniques in Patients with Chronic Kidney Failure in the Inpatient Room of the A. Yani Surabaya Islamic Hospital with anxiety nursing problems for 3 times. After carrying out 3 x nursing interventions in Chronic Kidney Failure patients, anxiety nursing problems can be resolved, the patient experiences changes from initially the patient has an anxiety score of 80 (severe anxiety) to 40 (not anxious). Spiritual Guided Imagery Relaxation Therapy is effective in reducing anxiety so that it can be used as an alternative to reduce anxiety in Chronic Kidney Failure patients and for ward nurses to be able to implement independent actions by implementing quick response actions so that patients can achieve optimal action.